Lei de responsabilidade educacional: direito fundamental à educação, regime jurídico administrativo e responsabilização dos agentes públicos - Neves, Danilo Trombetta [UNESP] (2015)
This work is linked to the research line Public Policy, School Organization and Teacher Education, of the Graduate Program in Education FCT-UNESP - Presidente Prudente/SP. In the scenario of the discussion on the creation of an Educational Responsibility Law the survey scrutinized the fundamental right to education by the Federal Constitution of 1988 and its implications in the legislative process in progress. Similarly, there was an emphasis on the study of the legal administrative system, since the lack of research on the subject undermines the view of the frame of providing the public education service. In the final part lays out an exegesis of the bills, especially the responsibility to be established in the educational field, aiming to verify their relevance to the promotion of basic public education with minimum quality standard. It ascertains the need for analysis and application of the principle of efficiency from the perspective of public administration as an organization and structure responsible for the provision of conditions for education to develop with minimum quality standard, besides the weighting of the actions of public officials throughout the chain, from the politicians to the education professionals themselves...